An app a day: Results of pre- and post-surveys of knowledge, attitudes, and practices (KAP) regarding antimicrobial stewardship principles among nurses who utilized a novel learning platform. Issue 1 (2nd March 2023) - Bobbitt, Laura J.; Cimino, Christo; Garvey, Kim V.; Craft, Leanna S.; Eichenseer, Nicole A.; Nelson, George E.
Abstract: Background: Nurses perform several functions that are integral for antimicrobial stewardship (AMS). However, nurses are underrepresented in research and underutilized in implementation of AMS interventions. The objective of this pilot study was to assess the effect of asynchronous microlearning on inpatient nursing staff knowledge, attitudes, and practices (KAP) regarding AMS principles. Methods: A team of pharmacists, physicians, and nurses developed 9 case-based, multiple-choice questions with accompanying educational explanations on associated AMS principles. One case was delivered to participants daily via an institutional web-based application (QuizTime). A KAP survey with 20 questions on a 5-point Likert scale was administered before and after the intervention. Survey results were compared using a Wilcoxon signed-rank test. Results: Participants' mean survey score after the intervention demonstrated statistically significant improvement for 18 (90%) of 20 items compared to before the intervention. Participants' confidence improved in key AMS activities: (1) differentiating between colonization and infection (mean difference, 0.63; P < .001), (2) identifying unnecessary urine cultures and inappropriate treatment of urinary tract infections (mean difference, 0.94; P < .001), (3) recognizing opportunities for intravenous to oral therapy conversion (mean difference, 1.07; P < .001), and (4) assessing for antibiotic-associated adverse effects (mean difference, 0.54; P < .001). Conclusions: Nursing education provided through an asynchronous, microlearning format via a mobile platform resulted in statistically significant improvement in most KAP topics. Nurses are integral members of a multidisciplinary AMS team, and novel education methods can help equip them with the necessary AMS tools. This pilot study forms the basis for expanded AMS educational efforts in all healthcare professionals.